AL-FARABI DAN IBN SINA (Kajian Filsafat Emanasi dan Jiwa dengan Pendekatan Psikologi) - Suprapto, Hadi (Jurnal Ilmiah Al-Hadi, 2017)
Not only the West, Islam also has a reliable philosophers who have exceptional quality thinking. However, a Muslim who deepens philosophy should not be separated from the rules of shari`at namely the provisions of the Qur'an and Al-Hadith. This is so that what will be poured from the results of his philosophy is not misleading other Muslims, because of course the philosophers get more attention even the results of their thinking learned by the next people. One of the most famous studies of philosophy is the theory of emanation, which says that the creation of this world is the radiance of the One. Many philosophers have given their view of this philosophy, given that a glimpse of the theory of emanation is very confusing even for those who are deep but not so deep still will be confused, because that's what philosophy is. Therefore, it is very necessary if in the lecture of Islamic Philosophy is also discussed about the theory of this emanation. To make our horizons of thinking and knowledge wider.